Studi mikrobiologis bakteri Escherichia coli dalam air Sungai Maros: Menilai kualitas air dan ancaman kesehatan - Sirajuddin, Nur Tasmiah (e-Journal BUDIDAYA PERAIRAN, 2025)
The quality of river water is an important concern in environmental health, especially related to pathogen bacterial contamination. The Maros River, located in Maros Regency, South Sulawesi Province, is used as a water source for various community needs. This study aimed to identify the presence of Escherichia coli bacteria and analyze the water quality of the Maros River based on microbiological and physicochemical parameters. Water samples were taken from three locations (upstream, middle, and downstream) and analyzed for E. coli colony count, pH, temperature, and turbidity. The results showed that the water of the Maros River was contaminated with E. coli bacteria, with the highest concentration found at the downstream site (2.5x104 CFU/100 mL), followed by the middle site (1.8x104 CFU/100 mL) and the upstream site (4.2x103 CFU/100 mL). Increased turbidity and temperature were also recorded at the downstream site. This decline in water quality is caused by pollution from domestic and industrial waste. Based on these results, better waste management is necessary to maintain water quality and public health.  Keywords: Escherichia coli, water quality, pollution, Maros River, waste management